Dieckol, a Major Marine Polyphenol, Enhances Non-Rapid Eye Movement Sleep in Mice via the GABAA-Benzodiazepine Receptor - Minseok Yoon; Jin-Soo Kim; Sangwoo Seo; Kiwon Lee; Kiwon Lee; Min Young Um; Jaekwang Lee; Jonghoon Jung; Suengmok Cho (Frontiers Media S.A., 2020)
We had previously demonstrated that phlorotannins, which are marine polyphenols, enhance sleep in mice via the GABAA-benzodiazepine (BZD) receptor. Among the constituents of phlorotannin, dieckol is a major marine polyphenol from the brown alga Ecklonia cava. Although phlorotannins are known to exert hypnotic effects, the sleep-enhancing effect of dieckol has not yet been determined. We evaluated the effect of dieckol on sleep-wake state of mice by analyzing electroencephalograms (EEGs) and electromyograms. Flumazenil, a GABAA-BZD antagonist, was used to investigate the molecular mechanism underlying the effects of dieckol on sleep. The polygraphic recordings and corresponding hypnograms revealed that dieckol accelerated the initiation of non-rapid eye movement sleep (NREMS); it shortened sleep latency and increased NREMS duration. According to the change in time-course, dieckol showed sleep-enhancing effects by increasing the amount of NREMS and decreasing wakefulness during the same hours. Additionally, sleep quality was evaluated by analyzing the EEG power density, and dieckol was found to not affect sleep intensity while zolpidem was found to reduce it. Finally, we treated mice with zolpidem or dieckol in combination with flumazenil and found the latter to inhibit the sleep-enhancing effect of dieckol and zolpidem, thereby indicating that dieckol exerts sleep-enhancing effects by activating the GABAA-BZD receptor, similar to zolpidem. These results implied that dieckol can be used as a promising herbal sleep aid with minimal side effects, unlike the existing hypnotics.